PENYULUHAN STRATEGI PEMASARAN PRODUK BIKA SINGKONG MASYARAKAT DESA CIMAYANG MELALUI MEDIA SOSIAL - Muhamad Ahbib Habibaka; M. Rizki Darmawan; Ayu Husna Kamilah; Erwin Hidayat; Acep Nugraha; Ermi Suryani (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
The purpose of this counseling is that the public is able to know and understand the marketing strategy of Bika Cassava Cimayang both offline and online through social media. The method of implementing the activities is carried out with a descriptive qualitative approach, with data collection techniques of observation, documentation, and interviews. The results showed that participants experienced an increase in knowledge about good marketing strategies, participants also got the motivation to change the marketing strategy of agricultural products by first managing agricultural products into food products, namely Bika Cassava Cimayang (SI MAYANG) and then implementing product marketing strategies both offline, namely by collaborating with Super Kue stores and online, by utilizing social media Instagram.